ANALISIS HUBUNGAN PENGGUNAAN KONTRASEPSI PADA WANITA DENGAN USIA MENOPAUSE - Vidayati, Lelly Aprilia (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2085)
Menopause is permanent cessation of menstruation after preceded by amenorhea for atleast one year. Menopausal age in women can occur at age 45-50 years but in somecircumstances can occur early or late. Age of menopause is influenced by several factors onethem the use of hormonal contraception. The purpose of this study is to determine therelationship of contraceptive use in women with age of menopause in Polindes Tebul Kec.Kwanyar.This research use Analytical design with Cross Sectional approach. The independentvariable is Contraception method and Dependent variable is age of menopause. The totalpopulation of 48 postmenopausal women from the study sample was 43 menopausal women.Sampling using simple random sampling technique. The instrument used is questionnaire.Univariate data analysis using frequency and bivariate distribution using chi square test withsignificant level Î± 0.05.The results showed that almost all menopausal women 43 people had a history of usinghormonal contraception that is 24 people (55.8%). While 21 men (48.9%) of menopausalwomen had normal menopause, respondents who had a history of using hormonalcontraceptives nearly half had normal menopause (48.9%). After chi square test withsignificant level Î± 0.05 obtained Ï Value: 0,008 <Î±: 0,05 so that H0 is rejected. This suggeststhat there is a relationship of contraceptive use in women with menopausal age.The conclusion of this study is that there is a relationship between contraceptive usein women with menopausal age, therefore it is advisable to menopause women to followposyandu elderly to increase knowledge about menopause.